Food controls to build workable human resource in Muslim countries for poverty reduction: An Islamic view - Uddin, Mohammad Nazim (IIUC Studies, 2022)
Food controls, also known as multi-functional physical and economic prevention, are significant for maintaining a healthy mind, body, and energy, as well as reducing consumption and poverty. As a result, the study aims to look at the impact of food controls on both human resource development and poverty reduction. The Holy Qur'an and Hadith, as well as the circumstances of Muslim nations, are utilized to describe food behavior and its influence on the workforce, poverty removal, and knowledge development. First, the investigation finds Mohammad's (PBUH) eating pattern and guiding principles, both of which are supported by the Qur'an in terms of food behavior and management. When it comes to eating behavior, the study finds that failing to learn Islam's guiding principles on food control leads to a plethora of problems such as poverty, sickness, greed, corruption, and waste. Those who waste less food and eat less are highly driven to enhance their health and knowledge generation abilities, both of which are advantageous to poverty reduction. As a result of decreased consumption and waste conservation, excess money and food may be used to help people get out of poverty. IIUC Studies Vol.18, December 2021: 33-46